Implementing the Certainty Factor Method in a Dental Disease Expert System - Gunawan, Andre; Islami, Fajrul (SAFE-Network, 2024)
Health, including dental and oral health, is a fundamental human necessity often overlooked by many. Dental and oral diseases can affect anyone unexpectedly, underscoring the critical need for timely professional advice from dentists based on symptoms presented by patients. Various factors contribute to the reluctance in seeking dental consultations, including inadequate awareness of oral health importance, financial constraints, and discomfort from lengthy wait times. This research proposes an Expert System utilizing the Certainty Factor method to diagnose dental diseases efficiently. The Certainty Factor method quantifies the certainty or uncertainty of facts within expert systems. Through computational analysis of multiple symptoms, the system accurately diagnosed a patient with Tooth Faktur disease with a high certainty level of 98.8%. Such an expert system promises to significantly aid dental professionals in diagnosing diseases promptly, facilitating appropriate treatment interventions.